METTL1 in human cancers: recognition of their functions, mechanisms and therapeutic value - Zhang, Xinyu; Chen, Yuan; Li, Min; Zhou, Xiaomeng; Song, Qingcui (Oncology Reviews, 2025)
Methyltransferase-like 1 (METTL1) is a methyltransferase that modulates the RNA methylation process and has been increasingly investigated in cancer research over the past decade. The review aims to summarize the diverse roles of METTL1 in various cancers, focusing on the mechanisms underlying tumorigenesis, progression, and metastasis. Furthermore, the therapeutic value and targeting strategies for METTL1 are also discussed to provide the foundation for further development of METTL1-targeted therapies. The article integrates recent research findings to highlight significant discoveries regarding METTL1, emphasizing its potential as a therapeutic target in cancer treatment.